Ways to Develop Education for Obtaining General Physical Qualities of Young Wrestlers Through Action Games - Begimkulov Oltiboy Jurayevich (Universitas Pendidikan Indonesia (UPI), 2023)
The modern stage of the development of the sport of wrestling is characterized by the increasing popularity of non-Olympic sports. Therefore, the International Wrestling Association (IKA) changes the rules of the competition with one goal - to activate the effective technical movements of wrestlers and increase their competitiveness. Here, the purpose of this study was to find out and demonstrate ways to develop education for getting the general physical qualities of young wrestlers through action games.